The Effect of Work–Life Balance, Employee Engagement, and Emotional Intelligence on Organizational Citizenship Behavior - Nabila Ardine Rihadatul Aisy; Ana Sofia Aryati (ITB AAS Indonesia Surakarta, 2026)
This explanatory quantitative study aims to analyze the effect of work–life balance, employee engagement, and emotional intelligence on organizational citizenship behavior among members of the Samapta Unit of the East Java Regional Police. This study was conducted at the Samapta Unit of the East Java Regional Police during the period of September–December 2025. Data were collected using a 5-point Likert-scale questionnaire that had passed validity and reliability testing and was distributed to all respondents who met the research criteria. After classical assumption testing, the collected data were analyzed using multiple linear regression with the assistance of SPSS version 29. The results indicate that work–life balance, employee engagement, and emotional intelligence simultaneously have a significant effect on organizational citizenship behavior. Partially, work–life balance, employee engagement, and emotional intelligence each have a significant effect on organizational citizenship behavior. These findings emphasize that balance between work and personal life, the level of members’ engagement in their duties, and the ability to manage emotions are critical factors in enhancing organizational citizenship behavior within a high-pressure policing work environment.